The Second World War : a people's history - Bourke, Joanna (OUP E-Books., 2001)
World War II surpassed all previous wars in the sheer cost of many millions of lives, most of them civilian. It left a world reeling from physical destruction on a scale never experienced till then, and from the psychological traumas of loss, of imprisonment and genocide, and permanent exile from home.; In this work, Joanna Bourke examines the events and outcomes in the vast number of places in which the War was fought: throughout Western and Central Europe, on the Eastern Front in the Soviet Union, in the Pacific, in Africa, in Asia. She shows where the strategic decisions came from and how they were implemented, but she also shows, through diary entries and recorded oral history, how ordinary people felt when they witnessed or heard of events, from the declaration of war on the radio to the mass murders carried out by Nazi soldiers in Russian villages.